SOLID WASTE SEGREGATION AS A STRATEGY FOR IMPROVED WASTE MANAGEMENT IN OKAKA COMMUNITY, BAYELSA STATE (2015)
Solid waste management is an established environmental health challenge in most societies. The heterogeneous nature of municipal solid waste makes its management particularly complex. Waste segregation which is key to proper solid waste management has not been adopted in the Nigerian society. Improper waste segregation could result in diarrheal diseases. The study was designed to assess solid waste segregation as a strategy for improved waste management in Okaka Community, Bayelsa State. A quasi-experimental study was adopted and multistage sampling was used to select (30) households. A semi-structured, self-administered questionnaire comprising respondents’ socio-demographic characteristics, 14-point knowledge scale and 14-point practice scale was used. The knowledge and practice scores were rated as poor (≤4), fair (4-8) and good (8). Jute sack bags without label or colour code were given to households to collect solid waste for 1 week. Wastes collected were characterised and weighed at pre-intervention. Thereafter, labelled colour coded jute sack bags (Black for degradable and White for non-degradable waste) were provided and training on its use was conducted for 2 weeks for the households. The questionnaire was re-administered to the selected respondents’ after intervention. Waste from the households were collected and weighed for 1 week as post-intervention SW segregation. Non-degradable waste was segregated, characterised and its components were weighed. Data were analysed using descriptive statistics, and t-test at p꞊0.05. Respondents’ age was 28.6±2.6 years. Educational status of respondents’ was non-formal (23.3%), primary (26.7%), secondary (20.0%) and tertiary (30.0%). Pre-intervention knowledge score of respondents’ was 2.7±0.2 while the practice score was 2.2±0.1. Respondents’ with poor and fair knowledge were 73.3% and 26.7%, while those with poor and fair practice were 70.0% and 30.0%, respectively. Pre-intervention SW segregated among the households were heterogeneous waste (5.0±0.5kg), metals (0.7±0.1kg), plastics (0.6±0.1kg), and glass (0.4±0.1kg). Respondents’ score for good knowledge was 9.4±0.2 while the practice score was 10.0±1.4 after intervention. Respondents’ knowledge score were good (64.3%) and poor (7.1%) while practice scores were good (93.3%) and poor (2.4%) after intervention. Respondents’ scores were fair for knowledge (28.6%) and practice (4.3%) after intervention. Knowledge and practice score were significant at pre and post- intervention. Waste segregated after intervention was degradables (2.2±0.6kg) and non-degradables (1.7±0.2kg). Components of non-degradable waste were nylon (0.4±0.1kg), metal (0.5±0.1kg), paper (0.4±0.1kg), plastic (0.2±0.1kg), glass (0.4±0.1kg), cloths (0.4±0.1kg), wood (0.5±0.1kg), shoes (0.6±0.1kg), e-waste (0.2±0.1kg), tetra-pack (0.2±0.1kg) and others (0.5±0.1kg). The knowledge and practice of solid waste segregation were improved after intervention. A lot of advocacy is needed to establish waste segregation practice. Public enlightenment, creation of buy-back recycling centres, community participation and training is highly recommended.